Optimization of Water-Ethanol Solvent Composition of Red Betel Leaf Extraction (Piper crocatum Ruiz & Pav) Using Simplex Latice Design Method on Antioxidant Activity - Sri Mulyaningsih; Ria Indah Pratami; Ichwan Ridwan Rais (Jurnal FARMASIMED (JFM), 2025)
Background: Free radicals cause oxidative stress that contributes to degenerative diseases and premature aging. Red betel leaves (Piper crocatum Ruiz & Pav) contain phenolic and flavonoid compounds with high antioxidant potential. Objective: This study aimed to determine the optimal water-ethanol solvent composition for red betel leaf extraction based on total phenol content and antioxidant activity. Method: Red betel leaf extraction was carried out by ultrasonication using several ratios of water and 96% ethanol solvents, then optimized using Simplex Lattice Design. Antioxidant activity was evaluated using the 2,2-azinobis(3-ethyl-benzothiazoline-6 ​​sulfonic acid (ABTS) method, which was measured using a microplate reader. Total phenol content was determined using a spectrophotometric method. Results: Red betel leaves extracted with water-ethanol solvent (0:100) showed the highest total phenol content of 152.23 ± 0.2 mg GAE/g with an IC50 of 74.18 ppm, which is categorized as strong. ANOVA analysis showed a significant model (p < 0.05) with R² > 0.90, confirming a strong correlation between phenolic content and antioxidant activity. SLD optimization produced a desirability value close to 1.0, indicating that ethanol is the most optimal solvent. Conclusion: Red betel leaves have strong potential as a source of natural antioxidants with ethanol as the optimal solvent for the extraction of bioactive compounds.